2012
DOI: 10.2174/138920212802510501
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Phosphorylated Histone H2AX Foci Formation and Removal of Cells Exposed to Low and High Linear Energy Transfer Radiation

Abstract: The use of particle ion beams in cancer radiotherapy has a long history. Today, beams of protons or heavy ions, predominantly carbon ions, can be accelerated to precisely calculated energies which can be accurately targeted to tumors. This particle therapy works by damaging the DNA of tissue cells, ultimately causing their death. Among the different types of DNA lesions, the formation of DNA double strand breaks is considered to be the most relevant of deleterious damages of ionizing radiation in cells. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…MSCs were able to efficiently repair these critical DNA lesions both after photon and after carbon ion irradiation as assessed by γH2AX immunostaining. While these cells exhibited less γH2AX foci directly after exposure to particle radiation than after photon treatment, carbon ion-induced foci appeared bigger; this finding corresponds to previously published data suggesting larger foci sizes along carbon ion tracks due to the increased creation of clustered DNA damage by densely ionizing particle radiation [ 19 ]. The ability of MSCs to swiftly repair both photon and particle-induced DNA double strand breaks was also reflected by the activation of the ataxia teleangiectasia-mutated (ATM)-dependent DNA damage signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…MSCs were able to efficiently repair these critical DNA lesions both after photon and after carbon ion irradiation as assessed by γH2AX immunostaining. While these cells exhibited less γH2AX foci directly after exposure to particle radiation than after photon treatment, carbon ion-induced foci appeared bigger; this finding corresponds to previously published data suggesting larger foci sizes along carbon ion tracks due to the increased creation of clustered DNA damage by densely ionizing particle radiation [ 19 ]. The ability of MSCs to swiftly repair both photon and particle-induced DNA double strand breaks was also reflected by the activation of the ataxia teleangiectasia-mutated (ATM)-dependent DNA damage signaling pathway.…”
Section: Discussionsupporting
confidence: 89%
“…One study showed that extracts derived from BRCA1-null MEFs exhibit significantly reduced end-joining activity compared with MEFs with wild-type BRCA1, providing initial insight into BRCA1's function in C-NHEJ [ 33 ]. Similarly, whole-cell extracts from the human BRCA1 -defective cell line HCC1937 had significantly reduced C-NHEJ activity compared with control cell extracts [ 34 ]. However, a number of studies suggest that BRCA1 is not required for C-NHEJ.…”
Section: Brca1 In C-nhejmentioning
confidence: 99%
“…High LET radiation induces complex DNA damage, a class of DNA lesions that includes two or more individual types of lesions within one or two helical turns of the DNA [16]. DNA sensing proteins localize to the sites of DNA DSB resulting in the formation of microscopically visible nuclear domains referred to as radiation-induced foci in the γ-H2AX assay [17].…”
Section: Discussionmentioning
confidence: 99%